An introduction to object - oriented systems analysis and design with UML and the unified process - Schach, Stephen R. (McGraw hill, 2004)
This text will be the first to present an object-oriented methodology from the outset for beginning Systems Analysis and Design students. It is the first book to introduce object-oriented methods without relying on classical methods to introduce key concepts or without requiring students to know Java or C++. It will presume no knowledge whatsoever about process modeling or data modeling. The widely used UML notation (unified modeling language) will be used throughout the book for all diagrams and model renderings.